Ekstraksi Flavour dari Tepung Ikan Layang (Decapterus sp.) Menggunakan Enzim Protease Biduri (Calotropis gigantea) - Jumardi Tondais; David Engelbert Sombo; Bella Anjelika Lalenoh; Mappiratu Mappiratu; Adrian Adrian; Eko Cahyono (Universitas Sriwijaya, 2020)
The development of science and technology has resulted in many mononatrium glutamate (MSG) flavorings which can have side effects for human health. The development of natural flavors needs to be done to reduce side effects for human health. Betell plant sap can be used as a source of protease enzymes that have the potential as active agents in flavor production. Flavors can be obtained from animal protein such as flying fish. The purpose of this study was to determine the best treatment of the enzyme biduri in producing flavored flying fish. This study uses a factorial completely randomized design (RALF) method with concentrations of 1.5%, 2.0%, and 2.5% slurry proteases with a hydrolysis duration of 30, 60, and 90 minutes. The results obtained indicate that the best water content at a concentration of 1.5% hydrolysis time is 90 minutes (47,84%), dissolved protein in concentration 2.5% hydrolysis time 60 minutes (86,83%), total amino acids in concentration 1.5% hydrolysis time 90 minutes (3,11%), and organoleptic value in concentration 1.5%.